Qualidade habitacional analisada quanto à adequação espacial : estudo de casos de condomínios horizontais produzidos em Cuiabá de 2000 a 2010 - Wendland, Mellyna Maria de Freitas (2014)
This work analyzes the quality of indoor environments of serial homes built in horizontal closed condominiums in Cuiaba, Mato Grosso State, between the years 2000 and 2010. The production, in focus, corresponds to housing for the people of the middle and upper social classes. For this procedure, adapted some national and international methods of housing quality assessment, with its appropriate corrections and conformations mainly Mato Grosso and Brazilian realities. The eleven indicators established were given a balancing test, in order to simplify the score of the sample universe. The result achieved confirms the identification of projects with higher and lower quality, provided for different spatial arrangements offered and areas. Of the 37 types analyzed, only four, 10.81 %, hadn’t a concept considered critical. This result shows that the quality of projects and the Brazilian building industry still leaves much to be desired, even when intended to higher economic and social classes. And yet, inadequate space arrangement may compromise the quality of the project regardless of the area. The development obtained through this method gives to this work an increasingly remarkable degree of importance as an inducer of a procedure capable of establishing criteria for design and housing product quality. It is expected that this research contribute to a better design, analysis and evaluation of isolated dwellings, apartment buildings and residential complexes and not only for housings in horizontal closed condominiums.